(untitled) - Brown, Peter (British, UK, 1998)
This collection of 22 tutorials is aimed at undergraduate students of veterinary pathology. Individual tutorials cover a variety of diseases affecting the kidney and the lower urinary tract and include a wide range of illustrations of gross and microscopic lesions. The tutorials includes many questions, often relating to illustrations, that prompt a student to consider a disease process or its effects. Two tutorials cover radiography of the kidney and urinary tract and three deal with urinalysis
Keywords: Urinary organs,Laboratory animals,Urologic diseases,Animals, laboratory; Diseases,Diseases,Veterinary